Investigation of the binding characteristics of anti-malarial drugs, mefloquine, lumefantrine and pyrimethamine to human serum albumin using spectroscopic and molecular docking methods / Kabiru Abubakar Musa - Kabiru , Abubakar Musa (2021)
Antimalarial drugs play a major role in the malaria therapy. Some of the FDA-approved antimalarial drugs, which are currently being used to treat malaria are mefloquine (MEF), lumefantrine (LUM) and pyrimethamine (PYR). Efficacy of a drug can be assessed based on its action on reaching a target tissue, which can be facilitated by a transport protein through circulatory system. Binding of MEF, LUM and PYR to human serum albumin (HSA), the main carrier protein in human blood circulation was investigated using fluorescence quenching titration, UV-vis absorption and circular dichroism (CD) spectroscopic techniques as well as molecular docking. Quenching of the protein (HSA) fluorescence induced by these drugs was characterized as static quenching, based on the decrease in the value of the Stern-Volmer constant, Ksv with increasing temperature, and/or the value of the bimolecular quenching rate constant, kq, which was found higher than the maximum kq value (2 × 1010 M ̶ 1 sec ̶ 1), reported for collisional quenching. These observations suggested the formation of drug-HSA complex, which was also confirmed from the UV-vis absorption spectral results. Values of the association constant, Ka for MEF/LUM/PYR ̶ HSA interactions were found to lie within the range, 1.32 ̶ 7.27 × 104 M ̶ 1, which indicated moderate binding affinity between these drugs and HSA. Non-covalent forces such as H-bonds, hydrophobic interactions and van der Waals forces were predicted to stabilize drug-HSA complexes, as revealed from thermodynamic data as well as molecular docking results. Far-UV and near-UV CD spectral results demonstrated smaller changes in both secondary and tertiary structures of HSA upon drug binding, while microenvironmental alterations around protein fluorophores (Trp and Tyr) were manifested by three-dimensional fluorescence spectra. Drug binding to HSA offered stability to the protein against thermal stress. The effect of a few metal ions on the drug binding characteristics of HSA was also noticed. Competitive drug displacement results as well as molecular docking analyses designated Sudlow’s Site I, located in subdomain IIA of HSA, as the preferred binding site of these drugs on HSA.